Austrian Muslims. The problems and achievements of social and political integration - E. V. Pinyugina (MGIMO University Press, 2012)
The national organization of Austrian Muslims in its first phase (1979–2000) was to improve dialogue between the state and Muslims, thereby making a contribution to the social integration of Muslims and their religious law and to social cohesion and so counteract social polarisation and segregation. Reality is more complicated: Muslims are not seen by others as part of Austrian society (right parties win up 18 to 30% by national and local elections) and their largest organizations are influenced by Turkish authorities or foreign fundamentalists. The construction of mosques and religious instruction at schools, supported by government as an important step towards the integration of Islam in Austria, can reach opposite goals, as the leaders of new Muslim’s political movements in Austria caution in mass-media. The activities of these new liberal movements can create a new scheme of Muslim-society cooperation and mutual understanding, in order to overcome irrational aggressive Islamophobia and sometimes reasonable Anti-Muslim prejudices.